2003
DOI: 10.1097/00005537-200312000-00030
|View full text |Cite
|
Sign up to set email alerts
|

Hypopharyngeal Acid Exposure: An Independent Risk Factor for Laryngeal Cancer?

Abstract: The present results do not support gastroesophago-hypopharyngeal reflux as being an independent risk factor for laryngeal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…A number of authors have identified a link between these diseases [7,11,30,31]; however, others have not [5,9,32,33]. Furthermore, due to small sample sizes and methodological limitations, the validity of many studies has been called into question.…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors have identified a link between these diseases [7,11,30,31]; however, others have not [5,9,32,33]. Furthermore, due to small sample sizes and methodological limitations, the validity of many studies has been called into question.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the current literature lacks consistency and clarity, since many of these studies were based on small number of cases (23, 24, 26, 32, 36, 38), did not adjust for potential confounding (23, 24, 26, 35, 38), or were cross-sectional in nature (23, 24, 26, 35, 38). However, the two case-control studies that examined medical history of GERD based on medical record review did not suffer from these issues and corroborate our findings with estimates in line with our own, with respective odds ratio estimates of 1.79 and 2.31 [19,23].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of GERD is estimated at 10%–20% in Western populations (20), with risk factors that include male gender, obesity, smoking and diet (18, 21). Reflux of gastric acid, a major risk factor for esophageal cancer (22), can reach beyond the esophagus into the laryngopharynx (known as laryngopharyngeal reflux) as demonstrated by 24-hour pH monitoring probes (2326). Although reflux has primarily been implicated in esophageal adenocarcinoma, esophageal squamous epithelium typically undergoes intestinal metaplasia in response to chronic exposure to gastric acid, which in turn develops into adenocarcinoma (27), whereas such a metaplastic transformation is not commonplace in the pharynx or larynx.…”
Section: Introductionmentioning
confidence: 99%
“…However, the difference in prevalence rates between LPR and GER in laryngeal cancer are significant in certain studies but not in others. Some studies reported that GER occurred in 25-67% of laryngeal cancer patients and the incidence was higher in the laryngeal cancer group compared with the control group (5). Copper et al (18) reported a 62% occurrence rate of LPR and 67% occurrence rate of pathologic GER in laryngeal and pharyngeal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since the mid-80's, a high frequency of acid reflux has been reported in laryngeal cancer patients who do not drink alcohol or smoke cigarettes, and this had lead to an increased interest in the relationship between laryngeal cancer and acid reflux (4). Also, it is well known that gastroesophageal reflux (GER) plays a role in the development of cancer of the lower esophagus, suggesting that laryngopharyngeal reflux (LPR) may also play a role in the development of laryngeal cancer (5-7). However, there is still a great deal of controversy surrounding the significance and role of LPR.…”
Section: Introductionmentioning
confidence: 99%